2001
DOI: 10.1098/rspb.2001.1627
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution in host–parasite systems: behavioural strategies of slave–making ants and their hosts

Abstract: Recently, avian brood parasites and their hosts have emerged as model systems for the study of hostp arasite coevolution. However, empirical studies of the highly analogous social parasites, which use the workers of another eusocial species to raise their own young, have never explicitly examined the dynamics of these systems from a coevolutionary perspective. Here, we demonstrate interpopulational variation in behavioural interactions between a socially parasitic slave-maker ant and its host that is consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
153
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(167 citation statements)
references
References 36 publications
11
153
3
Order By: Relevance
“…Nonetheless, hosts of insect social parasites and avian brood parasites show striking similarities in the trajectories and outcomes of their coevolutionary arms races [3]. Like avian hosts, social insects exhibit a range of morphological, behavioural and physiological adaptations to social parasites, which often co-occur in a single host species [9][10][11][12][13]. The apparent depth of these defence portfolios renders social parasitic hosts particularly suitable targets in the study of host defence portfolios [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, hosts of insect social parasites and avian brood parasites show striking similarities in the trajectories and outcomes of their coevolutionary arms races [3]. Like avian hosts, social insects exhibit a range of morphological, behavioural and physiological adaptations to social parasites, which often co-occur in a single host species [9][10][11][12][13]. The apparent depth of these defence portfolios renders social parasitic hosts particularly suitable targets in the study of host defence portfolios [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is not easy to quantify parasite pressure, because it depends on several parameters such as parasite prevalence, raid frequency and destructiveness as well as community composition. Previous studies have shown that parasite prevalence is very similar in the three focal communities (Table 1), but slavemaker colonies in NY seem to have a higher frequency of successful raids as compared to WV and OH (Foitzik et al 2001, Brandt & Foitzik 2004). …”
Section: Discussionmentioning
confidence: 95%
“…This suggests that the slavemaker might lead the arms race in NY, for example, by closely tracking host pupae profiles. In addition, it is possible that a higher number of raided host nests survive in WV, where slavemaker are less destructive during raids (Foitzik et al 2001). If so, slaves in WV might be more likely to have nests with relatives in the vicinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counter-measures are therefore expected to be selected, as recently shown by Foitzik et al (2001) studying three populations of the pair Protomognathus americanus/Leptothorax longispinosus. As a consequence of higher parasite pressure, the host population becomes more effective in defending against raiders.…”
Section: Discussionmentioning
confidence: 99%